Jurisprudential Choices for Resolving Madhhab Disagreements in Selected Prayer Rulings The Imam Abu Ḥanīfa Mosque (may Allah have mercy on him) as a Model: An Inductive Comparative Study - Asham, Ammar AbdulHussein (Journal of Islamic Sciences, 2025)
A number of large public mosques are marked by the coexistence of multiple madhhabs (legal schools). Among these is the Imam Abu Ḥanīfa Mosque (may Allah have mercy on him) in al-Aʿẓamiyyah. Such diversity can create confusion or difficulty for both the imam and the congregation in relation to certain juristic rulings of prayer.The central aim of this study is to establish guiding principles for selecting the most appropriate rulings—derived inductively—based on the overarching principle of the Shariʿah’s applicability across all times and places. This is pursued in a manner free from sectarian bias and in line with the objectives of the Shariʿah: to facilitate ease, remove hardship, unify the community, and avoid division.Methodologically, the study adopted an inductive approach to identify the issues relevant to its scope, followed by jurisprudential analysis to derive and assess the rulings most suitable for such mosques. Three issues—considered the most significant—were examined: the timing of the ʿAṣr adhān, the timing of the ʿIshāʾ adhān, and the Ṣalāt al-Ghāʾib (the funeral prayer performed in absentia).The findings indicate the following jurisprudential choices: (1) although the Ḥanafi school delays the ʿAṣr adhān, the position of the majority (jumhūr) was deemed more appropriate; (2) and (2) despite the Ḥanafi madhhab’s disapproval of performing Ṣalāt al-Ghāʾib, the Imam Abu Ḥanīfa Mosque adopted the alternative opinion, in recognition of influential figures in the community and as a means of acknowledging their contributions. All praise is due to Allah.
Keywords: jurisprudential choice; madhhab disagreements; Abu Ḥanīfa; prayer